Clinical Effectiveness of Dry Needling on Myofascial Trigger Points in Horses: A Prospective Algometric Controlled Study - Maria Calatayud-Bonilla; Jorge U. Carmona; Marta Prades (Animals)
Myofascial pain syndrome (MPS) is caused by trigger points (TrPs): hypersensitive spots in taut muscle bands that impair function and cause pain. Dry needling (DN) is a common treatment in humans, but evidence in horses is limited. This prospective, controlled study evaluated the effectiveness of DN in reducing TrP-related pain in the brachiocephalic muscle of horses. Of the 98 horses enrolled, 66 were allocated to a treatment group receiving weekly DN sessions for three weeks, while 32 were assigned to a control group with no intervention. Pain and function were assessed using pressure algometry, a numerical rating scale (NRS), a functional total test score (FTTS), and behavioral indicators including jump sign (JS), equine pain face (EPF), and local twitch responses (LTRs). Assessments were performed at baseline and at 0, 4, 24, and 72 h post-intervention. Results indicate a significant increase in pressure pain thresholds (p < 0.001), especially after the second and third sessions. Both NRS and FTTS improved significantly over time (p < 0.001), and LTRs progressively decreased. EPF and JS showed minimal variation. These results support the use of DN to reduce local muscle pain and improve function in horses with TrPs. Further robust studies are warranted to refine protocols and investigate long-term effects.